PENGENALAN RUANG SEJARAH (HISTORY ROOM) SEBAGAI MEDIA PEMBELAJARAN SEJARAH BAGI PENDIDIK DI KOTA METRO - Bobi Hidayat (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The history room is the important component in history teaching learning process. The history room can assist the teacher in giving a deep understanding about the student history awareness. But, in this case the using of history room by the teacher in teaching learning process isn’t optimal because of the room is limited. The limitation craeted some problem to the teacher so the socialization in managing and using the history room as a media in teaching and learning history was needed; and in the end hopefully the student history awareness can be improved. The methods used to introduce the history room were explanation and discussion. The methods choosed as the first step because most of the teacher didn’t have enough information in using the history room as the media in teaching and learning history. The result of this activity showed that the teacher understanding about history room improved. The understanding caused the teacher had a willing in developing and using the history room as a media in teaching and learning history. Although, there were some obstacles appeared in applying the history room in school, one of them was the support from the school but the communication with the school decision maker will be done to solve it.